PERANCANGAN JARINGAN MENGGUNAKAN ROUTER SWITCH CISCO PACKET TRACER PADA KANTOR DISKOMINFOTIK PROVINSI NUSA TENGGARA BARAT - Zulkarnaen, Isnaeni; Aliyah , Jannatun (Jurnal TAMBORA, 2021)
In the current era of globalization, technological developments are increasingly advanced, therefore human resources are required to be competent in various fields. To produce competent human resources. This study aims to design a computer network using a Cisco router switch at the West Nusa Tenggara Office of Information Communication and Statistics. The type of network designed refers to the LAN network (Local Area Network). This network design aims to facilitate IT personnel in completing work with stable and optimal signal strength with signals divided into each sub-sector. This research was conducted using qualitative methods by conducting direct observations in the field. The network development method used in this research is the NDLC (Network Development Life Cycle) method with the stages of analysis, design, simulation prototyping, implementation, monitoring, and management.